(untitled) (Global Journal of Cultural Studies, 2024)
The concepts of national culture play a substantial role in the everyday course of business in modern organizations. Globalization has created an environment where national culture has significant impacts in determining the success of multi-national organizations. This article presents a comprehensive literature review of the topic of culture and business. Focusing on two separate areas of culture (national culture & localized culture) the article seeks to provide clarity to the cultural concepts and finishes with how these concepts impact business decisions and processes. The article provides information to support the key concepts that culture is an important aspect of business and is crucial to the success of multi-national organizations.